Optimizing IT Governance in BTS.id: A COBIT 2019-Based Analysis of Design Factors - Tangka, George Morris William; Lompoliu, Erienika (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
Effective IT governance is critical for organizations to align technology with business objectives while ensuring risk management, compliance, and operational efficiency. As a technology-driven company, BTS.id faces challenges in managing IT risks, optimizing governance structures, and ensuring seamless alignment between IT initiatives and business strategy. This study analyzes IT governance implementation at BTS.id using the COBIT 2019 framework, focusing on assessing the organization's governance maturity level and identifying key design factors that influence IT governance effectiveness. The research employs document analysis, interviews, and surveys with key stakeholders to evaluate governance and management objectives, design factors, and capability levels. The findings indicate that while BTS.id has implemented IT governance practices, gaps remain in achieving an optimal governance structure. The highest priority areas include structured IT change management (BAI07), enterprise architecture (APO03), and project management (BAI11, BAI02), while risk management (APO12) and performance monitoring (MEA01) play a crucial supporting role. However, lower-priority governance objectives highlight areas for improvement, particularly in security management, vendor relationships, and compliance monitoring. The study underscores the importance of a structured approach to IT governance, emphasizing continuous performance monitoring, enhanced risk management, and strategic IT alignment.